Advances in nanomedicine for the treatment of Alzheimer's and Parkinson's diseases. (May 2016) - Hernando, Sara; Gartziandia, Oihane; Herran, Enara; Pedraz, Jose Luis; Igartua, Manoli; Hernandez, Rosa Maria
Alzheimer's disease and Parkinson's disease are the most common neurodegenerative diseases worldwide. Despite all the efforts made by the scientific community, current available treatments have limited effectiveness, without halting the progression of the disease. That is why, new molecules such as growth factors, antioxidants and metal chelators have been raised as new therapeutical approaches. However, these molecules have difficulties to cross the blood–brain barrier limiting its therapeutic effect. The development of nanometric drug delivery systems may permit a targeted and sustained release of old and new treatments offering a novel strategy to treat these neurodegenerative disorders. This review summarized the main investigated drug delivery systems as promising approaches to treat Alzheimer's disease and Parkinson's disease.